Fertirriego foliar orgánico en el rendimiento en Coriandrum sativum L. en organoponia. Loreto - Valera Garcia, Francisco Jose (2024)
The objective of this research was to evaluate the effect of organic foliar fertigation on the growth and yield of *Coriandrum sativum* L. (cilantro) cultivated using the organoponic technique. A comparative experiment was conducted between two fertigation treatments: CAF (organic foliar fertigation) and SAF (without fertigation), using a complete randomized design. Agronomic characteristics were analyzed, including plant height, root length, plant width, and weight of large plants per row. The results showed that the CAF treatment produced a significantly greater average plant height (6.40 cm more, p < 0.0001) and a higher width of the bundle (mean difference of 5.56 cm, p < 0.0001) compared to SAF. However, no significant differences were observed in root length. Regarding yield, the weight of large plants per row was also significantly higher in the CAF treatment (mean of 456 g compared to 160 g in SAF, p < 0.0001). These results suggest that the use of organic foliar fertigation (CAF) is an effective agricultural practice for improving the growth and production of cilantro, thereby promoting a more sustainable approach to agriculture.